Fragmented Narrative Technique as A Depiction of Trauma in Alice Munro's Dimensions - Hayati, Dzikrika Rahmatu (Journal of Language, Literature and Teaching, 2024)
This study examines the use of narrative techniques in depicting trauma and fragmented memories in the short story "Dimensions" by Alice Munro. This research aims to reveal how the narrative structure of the short story reflects the traumatic experience of the protagonist, Doree, by using Gérard Genette's narrative theory (1980) as an analytical framework. This research uses the short story "Dimensions" as the material object and is studied with a descriptive qualitative approach. The analysis reveals that Munro employs several narrative techniques—ellipsis, focalization, and analepsis—to depict trauma. Ellipsis conveys the characters' inability to access or fully process certain aspects of their traumatic experiences. The shifting focalization between external and internal perspectives reflects the dissociation and fragmented sense of identity often associated with trauma. Meanwhile, analepsis illustrates how characters continue to relive their past traumas through persistent flashbacks. This research reveals that the narrative structure of "Dimensions" functions not only as a storytelling tool, but also as a direct representation of the characters' own traumatic experiences.Keywords: Alice Munro, Trauma, Narrative Technique, Gérard Genette, Ellipsis, Focalization.